Ulama Perempuan Milenial: Wacana dan Legalitas Gerakan Kongres Ulama Perempuan Indonesia (KUPI) - Ghosiyah, Enok (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2023)
The conclusion of this article is: the perspective of millennial female clerics, the discourse and movement of female clerics who are members of the Indonesian Women's Ulama Congress. KUPI tries to offer an interpretation of the Koran with a feminist approach or justice and gender equality. The discourse and movement of millennial women scholars aims to find out the KUPI methodology. Because KUPI is a meeting place for the thoughts of female clerics who combine the traditions of Islamic boarding schools (traditional) and the traditions of higher education (reformers) as well as the meeting of classical studies based on turats with modernist studies based on modern science. In formulating thoughts or better known as the KUPI fatwa, it uses the Mubadalah, Hakiki Justice and Ma'ruf methodologies, so that the products of interpretation of the verses of the Qur'an and the products of study are easy and able to be accepted by all parties from various groups because apart from with the three methodologies, women's experience is the standard in formulating fatwas which of course refers to Islamic principlesrahmattan lil alamin, akhlakul karimah, nationality, humanity and universality.